Preparation method of sulfur-polyether copolymer composite positive electrode and lithium-sulfur battery

By using sulfur @ polyether type copolymer composite material in the positive electrode of lithium sulfur battery, the in-situ polymerization of ether monomers is used to form a semi-covered structure, which solves the problems of electron conduction ability and electrolyte penetration, and significantly improves the conductivity and cycling performance of the battery.

CN119601596AActive Publication Date: 2025-03-11QINGDAO UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411780501.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing conductive polymer composite sulfur cathode materials face problems in lithium-sulfur batteries with limited electron conductivity, poor electrolyte penetration, poor inhibition of electrode volume expansion, and weak polysulfide adsorption and fixation effects.

Method used

The preparation method of sulfur-polyether copolymer composite positive electrode is adopted, and in-situ polymerization of ether monomers on the surface of sulfur powder is formed to form a semi-covered core-shell structure, which enhances the ion transfer rate and electrochemical stability of the positive electrode, and at the same time, it uses materials such as conductive graphite, acetylene black and PVDF to enhance the conductivity.

Benefits of technology

It significantly improves the conductivity and chemical stability of lithium-sulfur batteries, and improves the cycling and rate performance under different current densities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601596A_ABST
    Figure CN119601596A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sulfur and polyether copolymer composite positive electrode and a lithium-sulfur battery, and the preparation method comprises the following steps: (1) mixing an ether monomer solution and a solvent, adding a lithium salt and an initiator, and stirring until the mixture is clear and transparent to obtain a precursor solution; (2) mixing the precursor solution with sulfur powder, putting the mixture into a pulping box for ball milling, and then drying to obtain a sulfur-polyether copolymer; (3) preparing positive electrode slurry by taking the sulfur-coated polyether copolymer, conductive graphite, acetylene black and polyvinylidene fluoride as raw materials; and blade-coating the positive electrode slurry on the carbon-coated aluminum foil, and drying to obtain the sulfur-polyether copolymer composite positive electrode. In the sulfur-coated polyether copolymer, the surface of partial sulfur powder is coated with the polyether polymer, so that the ion transmission rate and the electrochemical stability of a positive electrode can be enhanced; the surface of the residual sulfur powder is not coated by the polyether polymer, and the residual sulfur powder is exposed and can be combined with the conductive agent, so that the conductivity of the positive electrode is enhanced. According to the sulfur and polyether copolymer composite positive electrode, the lithium-sulfur battery can have excellent conductivity and chemical stability, and the cycle performance and the rate capability of the lithium-sulfur battery under different current densities can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a method for preparing a sulfur@polyether copolymer composite positive electrode and a lithium-sulfur battery. Background Art

[0002] Due to its special physical and chemical properties, the combination of polymers with active sulfur is still the key to achieve positive electrode modification. Polymers usually have rich functional groups, which have strong chemical adsorption effects on polysulfides and can effectively inhibit the shuttling effect of polysulfides. Conductive polymers are the most widely used polymers. Based on these advantages, more and more studies have been conducted on their use in lithium-sulfur batteries in recent years. There are two main forms of composites of conductive polymers and S: one is to form a core-shell structure of "polymer-encapsulated S", such as polythiophene (PTh) / S, polypyrrole (PPy) / S, polyvinylcarbazole (PVK) / S, polyaniline (PANi) / S and poly(3, 4-ethylenedioxythiophene) (PEDOT) / S composites, which mainly rely on the physical confinement of S in the polymer shell to stabilize the positive electrode and show good electrochemical performance. The other is the core-shell structure of "S-encapsulated polymer", such as compounding S to the surface of a conductive polymer matrix (mainly including PPy nanowires and nanotubes, PANi nanotubes and hollow PANi spheres, etc.) by melting or chemical deposition. The polymer plays the role of a conductor, dispersant, adsorbent and buffer for volume changes in the composite material, and provides a better carrier for the deposition of S.

[0003] Although conductive polymer composite sulfur cathode materials have shown significant advantages in the modification of lithium-sulfur battery cathodes, they still face the following challenges in practical applications: (1) The commonly used conductive polymers generally have a non-localized π-electron conjugated structure, which makes their ability to conduct electrons limited, and they still need to be further enhanced through copolymerization or doping. (2) Conductive polymer materials are generally very rigid, which is not conducive to the penetration of electrolytes and the formation of ion conductive networks, and the inhibitory effect on electrode volume expansion is not ideal. (3) The adsorption and fixation effect on polysulfides is still relatively weak, and more importantly, it cannot solve the problem of sulfur and lithium sulfide ion insulation. This defect will also greatly limit the practical application of composite materials in the modification of lithium-sulfur battery cathodes.

[0004] The purpose of this application is to develop a method for preparing a sulfur@polyether copolymer composite positive electrode and a lithium-sulfur battery to solve some of the defects in the above technical background. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a sulfur@polyether copolymer composite positive electrode and a lithium-sulfur battery. In the sulfur@polyether copolymer prepared in the present application, part of the sulfur powder surface is coated with a polyether polymer, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining sulfur powder surface is not coated with a polyether polymer, and the remaining sulfur powder is exposed, which can be combined with a conductive agent to enhance the conductivity of the positive electrode. The sulfur@polyether copolymer composite positive electrode of the present application can make the lithium-sulfur battery have excellent conductivity and chemical stability, and can greatly improve the cycle performance and rate performance of the lithium-sulfur battery at different current densities.

[0006] To this end, the present invention provides a method for preparing a sulfur@polyether copolymer composite positive electrode, comprising: (1) mixing an ether monomer solution and a solvent, adding a lithium salt and an initiator, and stirring until the solution is clear and transparent to obtain a precursor solution; (2) Mixing the precursor solution and sulfur powder into a beating box for ball milling, and then drying to obtain a sulfur@polyether copolymer; (3) A positive electrode slurry is prepared using sulfur@polyether copolymer, conductive graphite, acetylene black and polyvinylidene fluoride (PVDF) as raw materials; the positive electrode slurry is coated on a carbon-coated aluminum foil and dried to obtain a sulfur@polyether copolymer composite positive electrode.

[0007] Preferably, in step (1), the ether monomer includes aziridine crosslinker TTMAP, 1,3-dioxolane DOL and / or glycidyl 2,2,3,3-tetrafluoropropyl ether.

[0008] Preferably, in step (1), the solvent is N-methylpyrrolidone (NMP), and the ratio of the volume of the ether monomer solution to the volume of the solvent is (0.5-1.5):(5-20).

[0009] Preferably, in step (1), the lithium salt comprises lithium bis(trifluoromethanesulfonyl)imide LiTFSI and / or lithium hexafluorophosphate LiPF 6 , the molar ratio of the ether monomer to the lithium salt is 0.9:1-1.2:1.

[0010] Preferably, in step (1), the initiator comprises lithium bis(trifluoromethanesulfonyl)imide LiTFSI and / or lithium hexafluorophosphate LiPF 6 , the molar ratio of ether monomer and initiator is (0.8-1.5):(1-2).

[0011] Preferably, in step (2), the ratio of the volume of the ether monomer solution to the mass of the sulfur powder is (150-250) uL: (0.5-1.5) g.

[0012] Preferably, in step (2), the ball milling speed is 200-400 r / min, and the ball milling time is 40-55 h; the drying process includes: drying in a blast oven for 10-15 h, and then drying in a vacuum oven for 10-15 h.

[0013] Preferably, in step (3), the mass ratio of sulfur@polyether copolymer: conductive graphite: acetylene black: PVDF is (60-70): (10-20): (10-20): (3-9).

[0014] Preferably, in step (3), the thickness of the sulfur@polyether copolymer composite positive electrode is 200-300 um and the diameter is 7-15 mm.

[0015] The present application also provides a lithium-sulfur battery, comprising a lithium negative electrode, a polyethylene separator, and a positive electrode, wherein the positive electrode is a sulfur@polyether copolymer composite positive electrode prepared by the preparation method of the sulfur@polyether copolymer composite positive electrode.

[0016] Compared with the prior art, the advantages and positive effects of the present invention include: (1) The preparation process of the sulfur@polyether copolymer of the present application is carried out at room temperature, has low environmental requirements, and does not require the preparation of a template in advance, and has the advantages of being simple, easy to operate, and energy-saving. The production efficiency of the sulfur@polyether copolymer is high and can be mass-produced.

[0017] (2) The ether monomers of the present application can be effectively and uniformly polymerized in situ on the surface of the sulfur powder, achieving controllable coating, and ensuring the formation of a sulfur@polyether copolymer with a semi-coated morphology and a core-shell structure. In the sulfur@polyether copolymer prepared in the present application, part of the sulfur powder surface is coated with the polyether polymer, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining part of the sulfur powder surface is not coated with the polyether polymer, and the remaining part of the sulfur powder is exposed, which can be combined with the conductive agent to enhance the conductivity of the positive electrode.

[0018] (3) The ether monomer of the present application is preferably TTMAP. TTMAP has excellent ion conductivity, high thermal stability, excellent chemical stability, and low volatility. It can effectively block the dissolution of sulfur and polysulfides while increasing the ion conductivity of sulfur. Secondly, the polyether polymer TTMAP has excellent flexibility and mechanical stability, which is conducive to the penetration of electrolyte and the formation of ion conductive network. It has a good buffering effect on the volume expansion and / or volume contraction of sulfur during battery charging and discharging, ensuring the structural stability of the positive electrode, and can greatly improve the cycle performance and rate performance of lithium-sulfur batteries at different current densities. In addition, the polyether polymer TTMAP contains abundant ester groups C=O and nitrogen rings, which have excellent fixation and absorption effects on polysulfides and can effectively block the dissolution of polysulfides.

[0019] (4) The sulfur@polyether copolymer synthesized by the ring-opening copolymerization reaction in the present application can produce obvious swelling phenomenon and good gel behavior in the organic electrolyte. It can effectively block the dissolution of sulfur and polysulfide while promoting the penetration of electrolyte. At the same time, its excellent mechanical stability can effectively alleviate the volume strain of the electrode. The lithium-sulfur battery assembled with the sulfur@polyether copolymer composite positive electrode has greatly improved the cycle performance and rate performance at different current densities. More importantly, the ether oxygen group (-COC-) possessed by the polyether polymer is conducive to the dissociation of lithium salts, and can achieve efficient lithium ion transmission by "complexation-decomplexation" with lithium ions.

[0020] (5) During the entire coating preparation process, no additional substances are introduced; LiTFSI and LiPF 6 They are all common lithium salts in lithium batteries. They will not react with the electrolyte and will not cause side reactions in the battery, making them safer.

[0021] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM morphology image of the sulfur@polyether copolymer composite positive electrode prepared in Example 1 of the present invention; Figure 2 This is a TEM morphology image of the sulfur@polyether copolymer composite positive electrode prepared in Example 1 of the present invention; Figure 3 This is the TEM morphology of sulfur powder; Figure 4 The figure is a rate performance test diagram of the lithium-sulfur battery of Example 2 of the present invention and Comparative Example 1; Figure 5 The graphs are the cycle performance test graphs of the lithium-sulfur batteries of Example 2 and Comparative Example 1 of the present invention; Figure 6 This is the visual absorption test chart of the ether polymer TTMAP for polysulfide solution. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Meanwhile, after reading the present invention, those skilled in the art may make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0024] The method for preparing the sulfur@polyether copolymer composite positive electrode of the present invention comprises: (1) mixing an ether monomer solution and a solvent, adding a lithium salt, and stirring until the solution is clear and transparent to obtain a precursor solution; The ether monomer includes at least one of propidium crosslinking agent TTMAP, 1,3-dioxolane DOL, and glycidyl 2,2,3,3-tetrafluoropropyl ether.

[0025] The ether monomer of the present application is preferably TTMAP, which has excellent ion conductivity, high thermal stability, excellent chemical stability, and low volatility. It can effectively block the dissolution of sulfur and polysulfides while increasing the ion conductivity of sulfur. Secondly, the polyether polymer TTMAP has excellent flexibility and mechanical stability, which is conducive to the penetration of electrolyte and the formation of ion conductive network. It has a good buffering effect on the volume expansion and / or volume contraction of sulfur during battery charging and discharging, ensures the structural stability of the positive electrode, and can greatly improve the cycle performance and rate performance of lithium-sulfur batteries at different current densities. In addition, the polyether polymer TTMAP contains abundant ester groups C=O and nitrogen rings, which have excellent fixation and absorption effects on polysulfides and can effectively block the dissolution of polysulfides.

[0026] The solvent is N-methylpyrrolidone NMP, and the ratio of the volume of the ether monomer solution to the volume of the solvent is (0.5-1.5): (5-20). Preferably, the ratio of the volume of the ether monomer solution to the volume of the solvent is (0.8-1.2): (8-15).

[0027] The solvent of the present application can make the ether monomer solution and sulfur powder fully and evenly mixed, and can make the ether monomer effectively and evenly polymerize in situ on the surface of sulfur powder to form a polyether copolymer with semi-encapsulated morphology and core-shell structure.

[0028] Lithium salts include lithium bis(trifluoromethanesulfonyl)imide LiTFSI and / or lithium hexafluorophosphate LiPF 6 The lithium salt used in the present application has high electrochemical stability and conductivity, and has a low probability of side reactions, and can provide electrochemical stability and conductivity for lithium-sulfur batteries.

[0029] The molar ratio of the ether monomer to the lithium salt is 0.9:1-1.2:1, and preferably, the molar ratio of the ether monomer to the lithium salt is 1:1; the lithium salt can improve the ionic conductivity and electrochemical stability of the polyionic liquid copolymer to the greatest extent.

[0030] The initiator can be lithium hexafluorophosphate LiPF 6 , LiPF 6 It is also a common lithium salt with good thermal stability and solubility, which can improve battery stability and conductivity. 6 It can also be used as an initiator to induce the ring opening of ether monomers and complete polymerization on the surface of sulfur powder.

[0031] The molar ratio of the ether monomer to the initiator is (0.8-1.5):(1-2), preferably, the molar ratio of the ether monomer to the initiator is (0.9-1.2):(1.3-1.7).

[0032] The initiator of the present application can initiate the ring-opening polymerization of ether monomers, so that the ether monomers are polymerized uniformly on the surface of sulfur powder, while avoiding the generation of bubbles caused by excessive polymerization of ether monomers, and ensuring the formation of a polyether copolymer with a semi-encapsulated morphology and a core-shell structure.

[0033] By adjusting the amount of lithium salt and initiator used, the present application can make the ether monomers effectively and evenly polymerize in situ on the surface of the sulfur powder, realize the controllability of the coating, and ensure the formation of a polyether copolymer with a semi-coated morphology and a core-shell structure. In the polyether copolymer prepared in the present application, part of the sulfur powder surface is coated with the ether polymer, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining part of the sulfur powder surface is not coated with the ether polymer, and the remaining part of the sulfur powder is exposed, which can be combined with the conductive agent to enhance the conductivity of the positive electrode.

[0034] (2) Mixing the precursor solution and sulfur powder into a beating box for ball milling, and then drying to obtain a sulfur@polyether copolymer; The volume ratio of the ether monomer solution to the mass ratio of the sulfur powder is (150-250) uL: (0.5-1.5) g, and preferably, the volume ratio of the ether monomer solution to the mass ratio of the sulfur powder is (180-220) uL: (0.8-1.2) g. The ether monomer can be effectively and uniformly polymerized in situ on the surface of the sulfur powder to form a polyether copolymer with a semi-encapsulated morphology and a core-shell structure.

[0035] The ball milling speed is 200-400 r / min, and the ball milling time is 40-55h. Through ball milling, the ether monomers can be effectively and uniformly polymerized in situ on the surface of the sulfur powder to form a polyether copolymer with a semi-encapsulated morphology and a core-shell structure.

[0036] The drying process includes: drying in a forced air oven for 10-15 hours, and then drying in a vacuum oven for 10-15 hours.

[0037] (3) A positive electrode slurry is prepared using sulfur@polyether copolymer, conductive graphite, acetylene black and polyvinylidene fluoride (PVDF) as raw materials; the positive electrode slurry is coated on a carbon-coated aluminum foil and dried to obtain a sulfur@polyether copolymer composite positive electrode.

[0038] The mass ratio of sulfur@polyether copolymer: conductive graphite: acetylene black: PVDF is (60-70): (10-20): (10-20): (3-9). When the reaction is carried out within the above mass ratio range, a positive electrode with a stable structure can be obtained, which can improve the ion transfer rate, conductivity and electrochemical stability of the positive electrode.

[0039] The conductive graphite and acetylene black of the present application can effectively solve the problem of sulfur's non-conductivity and effectively enhance the conductivity of the positive electrode.

[0040] The binder PVDF of the present application can ensure the effective adhesion of the sulfur@polyether copolymer, conductive graphite and acetylene black to each other, prevent the sulfur@polyether copolymer and / or conductive graphite and / or acetylene black from falling off after drying, and ensure the formation of a sulfur@polyether copolymer composite positive electrode with a stable structure.

[0041] The thickness of the sulfur@polyether copolymer composite positive electrode is 200-300 um and the diameter is 7-15 mm.

[0042] The present invention also provides a lithium-sulfur battery, which is assembled into a button lithium-sulfur battery using a lithium negative electrode, a polyethylene separator, a lithium-sulfur electrolyte and a sulfur@polyether copolymer composite positive electrode prepared by the preparation method of the sulfur@polyether copolymer composite positive electrode described in the present invention.

[0043] The advantages and positive effects of the present invention include: (1) The preparation process of the sulfur@polyether copolymer of the present application is carried out at room temperature, has low environmental requirements, and does not require the preparation of a template in advance, and has the advantages of being simple, easy to operate, and energy-saving. The production efficiency of the sulfur@polyether copolymer is high and can be mass-produced.

[0044] (2) The ether monomers of the present application can be effectively and uniformly polymerized in situ on the surface of the sulfur powder, achieving controllable coating, and ensuring the formation of a sulfur@polyether copolymer with a semi-coated morphology and a core-shell structure. In the sulfur@polyether copolymer prepared in the present application, part of the sulfur powder surface is coated with the polyether polymer, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining part of the sulfur powder surface is not coated with the polyether polymer, and the remaining part of the sulfur powder is exposed, which can be combined with the conductive agent to enhance the conductivity of the positive electrode.

[0045] (3) The ether monomer of the present application is preferably TTMAP. TTMAP has excellent ion conductivity, high thermal stability, excellent chemical stability, and low volatility. It can effectively block the dissolution of sulfur and polysulfides while increasing the ion conductivity of sulfur. Secondly, the polyether polymer TTMAP has excellent flexibility and mechanical stability, which is conducive to the penetration of electrolyte and the formation of ion conductive network. It has a good buffering effect on the volume expansion and / or volume contraction of sulfur during battery charging and discharging, ensuring the structural stability of the positive electrode, and can greatly improve the cycle performance and rate performance of lithium-sulfur batteries at different current densities. In addition, the polyether polymer TTMAP contains abundant ester groups C=O and nitrogen rings, which have excellent fixation and absorption effects on polysulfides and can effectively block the dissolution of polysulfides.

[0046] (4) The polyether copolymer synthesized by ring-opening copolymerization can produce obvious swelling phenomenon and good gel behavior in organic electrolyte. It can effectively block the dissolution of S and polysulfide while promoting electrolyte penetration. At the same time, its excellent mechanical stability can effectively alleviate the volume strain of the electrode. The cycle performance and rate performance of the battery assembled by TTMAP@S at different current densities have been greatly improved. More importantly, the ether group (-COC-) of the polyether polymer is conducive to the dissociation of lithium salts, and can achieve efficient lithium ion transmission by "complexation-decomplexation" with lithium ions.

[0047] (5) During the entire coating preparation process, no additional substances are introduced; LiTFSI and LiPF 6 They are all common lithium salts in lithium batteries. They will not react with the electrolyte and will not cause side reactions in the battery, making them safer. Example 1

[0048] The preparation method of the sulfur@polyether copolymer composite positive electrode of this embodiment includes: (1) Mix 200 uL of trifunctional aziridine crosslinker TTMAP solution with 2000 uL of N-methylpyrrolidone NMP solution, and add 0.058 g of LiTFSI and 0.046 g of LiPF 6 , and stir until clear and transparent to obtain a precursor solution.

[0049] (2) The precursor solution was mixed with 1 g of S powder and placed in a beating box. The mixture was ball-milled at a speed of 300 r / min for 48 h. The mixture was taken out and dried in a forced air oven for 12 h, and then in a vacuum oven for 12 h to obtain a sulfur@polyether copolymer.

[0050] (3) Using polyvinylidene fluoride (PVDF) as a binder, a positive electrode slurry was prepared in the ratio of sulfur@polyether copolymer: conductive graphite: acetylene black: PVDF = 65:15:15:5. Then, a 250 um thick positive electrode slurry was scraped onto a carbon-coated aluminum foil, dried, and cut into a disc with a diameter of 10 mm as the positive electrode.

[0051] Figure 1 This is a SEM morphology of the sulfur@polyether copolymer composite positive electrode prepared in Example 1 of the present invention. Figure 1 From the SEM image, it can be seen that there is a semi-coated structure on the surface of the sulfur powder. The coating layer is the ether polymer TTMAP. The presence of the polymer can improve the ion conductivity of sulfur. At the same time, it can be seen that there are parts on the surface of the sulfur powder that are not coated by the polymer. The uncoated sulfur powder can be combined with the conductive agent when preparing the positive electrode. That is, part of the sulfur powder surface is coated with the polyether polymer, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining part of the sulfur powder surface is not coated with the polyether polymer, and the remaining part of the sulfur powder is exposed, which can be combined with the conductive agent to enhance the conductivity of the positive electrode.

[0052] The sulfur@polyether copolymer composite positive electrode of the present application is a semi-coated structure. It can also be seen from the figure that the coating layer polyether polymer coats the sulfur powder more evenly.

[0053] Figure 2 This is a TEM morphology of the sulfur@polyether copolymer composite positive electrode prepared in Example 1 of the present invention. Figure 3 is the TEM morphology of sulfur powder; Figure 2 and Figure 3 By comparison, it can be seen that the sulfur powder surface of the sulfur@polyether copolymer composite positive electrode prepared in Example 1 has a semi-coated structure, and the coating layer is the ether polymer TTMAP. The presence of the polymer can improve the ion conductivity of sulfur. At the same time, it can be seen that there is a part on the surface of the sulfur powder that is not coated by the polymer, and the uncoated sulfur powder can be combined with the conductive agent when preparing the positive electrode. Figure 3 This is the TEM morphology of sulfur powder. It can be seen that the surface of pure sulfur is smooth and flat, and the surface of pure sulfur is not covered with other components.

[0054] Figure 6 This is a visual absorption test chart of the polyether polymer TTMAP of the present application to polysulfide solution, Figure 6 (a) is the initial photograph of adding polymer TTMAP into the polysulfide solution; Figure 6 (b) is a photo of polymer TTMAP immersed in polysulfide solution for 24 h; Figure 6 (c) is a photo of polymer TTMAP immersed in polysulfide solution for 48 hours. Figure 6It can be seen that after the polymer TTMAP is added to the polysulfide solution, the color of the solution gradually becomes lighter, which can illustrate that the polyether polymer TTMAP of the present application has an excellent adsorption and fixation effect on polysulfide. Example 2

[0055] The lithium-sulfur battery of this embodiment includes: the sulfur@polyether copolymer composite positive electrode of Example 1 as the positive electrode, a lithium sheet as the negative electrode, 19 mm polyethylene (PE) as the separator, and a button cell assembled using a lithium-sulfur electrolyte.

[0056] Comparative Example 1 The lithium-sulfur battery of this comparative example includes: sulfur S as a positive electrode, a lithium sheet as a negative electrode, 19 mm polyethylene (PE) as a separator, and a button cell assembled using a lithium-sulfur electrolyte.

[0057] Figure 4 The figure is a rate performance test diagram of the lithium-sulfur battery of Example 2 of the present invention and Comparative Example 1, and the figure is a rate performance test diagram of the lithium-sulfur battery after 10 cycles at different current densities (0.1C, 0.2C, 0.5C, 1C, 2C, 0.1C). Figure 4 It can be seen that at each current density, the capacity of the lithium-sulfur battery in Example 2 is higher than that of the lithium-sulfur battery in Comparative Example 1; and when the current density gradually increases and finally returns to the initial 0.1C, the capacity recovery of the lithium-sulfur battery in Example 2 is good.

[0058] Figure 5 This is a cycle performance test diagram of the lithium-sulfur battery of Example 2 of the present invention and Comparative Example 1. This is a cycle performance test diagram of the battery charge and discharge cycle of 300 times at a current density of 0.5C. Figure 5 It can be seen that the lithium-sulfur battery of Example 2 has high capacity, small attenuation, high retention rate, and excellent cycle performance.

[0059] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.

Claims

1. A method for preparing a sulfur@polyether copolymer composite positive electrode, characterized in that: include: (1) mixing an ether monomer solution and a solvent, adding a lithium salt and an initiator, and stirring until the solution is clear and transparent to obtain a precursor solution; (2) Mixing the precursor solution and sulfur powder into a beating box for ball milling, and then drying to obtain a sulfur@polyether copolymer; (3) A positive electrode slurry is prepared using sulfur@polyether copolymer, conductive graphite, acetylene black and polyvinylidene fluoride (PVDF) as raw materials; the positive electrode slurry is coated on a carbon-coated aluminum foil and dried to obtain a sulfur@polyether copolymer composite positive electrode.

2. The method for preparing the sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the ether monomers include aziridine crosslinking agent TTMAP, 1,3-dioxolane DOL and / or glycidyl 2,2,3,3-tetrafluoropropyl ether.

3. The method for preparing the sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the solvent is N-methylpyrrolidone (NMP), and the ratio of the volume of the ether monomer solution to the volume of the solvent is (0.5-1.5):(5-20).

4. The method for preparing the sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide LiTFSI and / or lithium hexafluorophosphate LiPF6, and the molar ratio of the ether monomer to the lithium salt is 0.9:1-1.2:

1.

5. The method for preparing the sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the initiator includes lithium bis(trifluoromethanesulfonyl)imide LiTFSI and / or lithium hexafluorophosphate LiPF6, and the molar ratio of the ether monomer to the initiator is (0.8-1.5):(1-2).

6. The method for preparing the sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (2), the ratio of the volume of the ether monomer solution to the mass of the sulfur powder is (150-250) uL: (0.5-1.5) g.

7. The method for preparing a sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (2), the ball milling speed is 200-400 r / min and the ball milling time is 40-55h; The drying process includes: drying in a forced air oven for 10-15 hours, and then drying in a vacuum oven for 10-15 hours.

8. The method for preparing the sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (3), the mass ratio of sulfur@polyether copolymer: conductive graphite: acetylene black: PVDF is (60-70): (10-20): (10-20): (3-9).

9. The method for preparing the sulfur@polyether copolymer composite positive electrode according to claim 1, characterized in that: In the step (3), the thickness of the sulfur@polyether copolymer composite positive electrode is 200-300 um and the diameter is 7-15 mm.

10. A lithium-sulfur battery comprising a lithium negative electrode and a polyethylene separator, characterized in that: It also includes a positive electrode, wherein the positive electrode is a sulfur@polyether type copolymer composite positive electrode prepared by the preparation method of the sulfur@polyether type copolymer composite positive electrode according to any one of claims 1-9.

Citation Information

Patent Citations

  • Sulphidepolymer coated sulfur / carbon composite material and preparation method thereof

    CN104241612A

  • Electrode composite material, its preparation method, positive electrode, battery possessing positive electrode

    CN104347850A

  • Lithium-sulfur battery sulfur electrode material of hyperbranched polymer network and preparation method

    CN108376773A

  • High-sulfur supported lithium-sulfur battery positive electrode, preparation method of lithium-sulfur battery positive electrode, and lithium-sulfur battery

    CN109346678A